Public opinion on the accountability of local government : a case study of DBKK / Mohd Fariz Azwan Abdul Wahab and Mohd Hafizul Sindran - Abdul Wahab, Mohd Fariz Azwan; Sindran, Mohd Hafizul (2013)
This research is an attempt to understand the public opinion on the accountability local government which is focused on Dewan Bandaraya Kata Kinabalu (DBKK). There is an increasing demand of accountability and transparency from the public towards the local government recently. The objective of this research is to find out what are the opinions of the public towards the accountability of local government. The research method consists of primary and secondary data such as the distribution of questionnaires among the public around Kata Kinabalu and document review from both online and offline resources. All of the information gathered is important to bring some ideas to conduct the research. This research develops a quantitative instrument to find out what is the public opinion on the accountability of the local government.